PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Hajijah, Siti; Melati, Husna Amalya; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research is conducted based on the finding of the low level of students’ critical thinking skills in chemistry subject. The purposes of this research are to determine whether there is a significant difference in critical thinking between those who were taught by applying problem solving learning model and those who were not in thermochemistry topic and determine the effect of problem solving learning model towards students’ critical thinking skills. This research used Non Randomize Control Group Design type of quasi- experimental design. The samples were taken using Random Sampling Technique with the result XI science A class was experiment group while XI science C was control group. According to Mann Whitney U test (α = 5%) and calculation of effect size, P-value was 0.001 and the effect was 0.81 respectively. These data show that there is a significant difference in critical thinking skills between those group and Problem Solving model has a large effect on improving students’ critical thinking skills. Keywords: Critical Thinking, Problem Solving, Thermochemistry